Characterizing the ASD–ADHD phenotype: measurement structure and invariance in a clinical sample. (27th March 2022) - Krakowski, Aneta D.; Cost, Katherine Tombeau; Szatmari, Peter; Anagnostou, Evdokia; Crosbie, Jennifer; Schachar, Russell; Duku, Eric; Georgiades, Stelios; Ayub, Muhammad; Kelley, Elizabeth; Nicolson, Rob; Pullenayegum, Eleanor; et al.
Abstract : Background: Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) have considerable overlap, supporting the need for a dimensional framework that examines neurodevelopmental domains which cross traditional diagnostic boundaries. In the following study, we use factor analysis to deconstruct the ASD–ADHD phenotype into its underlying phenotypic domains and test for measurement invariance across adaptive functioning, age, gender and ASD/ADHD clinical diagnoses. Methods: Participants included children and youth (aged 3–20 years) with a clinical diagnosis of ASD ( n  = 727) or ADHD ( n  = 770) for a total of 1, 497 participants. Parents of these children completed the Social Communication Questionnaire (SCQ), a measure of autism symptoms, and the Strengths and Weaknesses of ADHD and Normal Behaviour (SWAN) questionnaire, a measure of ADHD symptoms. An exploratory factor analysis (EFA) was performed on combined SCQ and SWAN items. This was followed by a confirmatory factor analysis (CFA) and tests of measurement invariance. Results: EFA revealed a four‐factor solution (inattention, hyperactivity/impulsivity, social‐communication, and restricted, repetitive, behaviours and interests (RRBI)) and a CFA confirmed good model fit. This solution also showed good model fit across subgroups of interest. Conclusions: Our study shows that a combined ASD–ADHD phenotype is characterized by two latent ASD domains (social communication and RRBIs) and two latent ADHD domains (inattention and hyperactivity/impulsivity). We established measurement invariance of the derived measurement model across adaptive functioning, age, gender and ASD/ADHD diagnoses.